2017
DOI: 10.5604/01.3001.0010.4855
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Beta-Lactamase Producing Pseudomonas aeruginosa in a Healthcare Setting in Alexandria, Egypt

Abstract: Pseudomonas aeruginosa has emerged as a major healthcare associated pathogen that creates a serious public health disaster in both developing and developed countries. In this work we aimed at studying the occurrence of metallo-beta-lactamase (MBL) producing P. aeruginosa in a healthcare setting in Alexandria, Egypt. This cross sectional study included 1583 clinical samples that were collected from patients admitted to Alexandria University Students' Hospital. P. aeruginosa isolates were identified using standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
3
13
2
Order By: Relevance
“…A study from Iran that included 19 MBL-producing P. aeruginosa reported that 31.5% of their isolates carried the bla VIM gene and 10.5% carried bla IMP , which was higher than that reported in this study [22]. In contrast to our study, a study from Egypt reported that none of their P. aeruginosa was positive for the bla VIM gene [20]. In the present study, 9.4% of our isolates were positive for the bla NDM-1 gene, which is lower than that reported from India (27%) [31].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A study from Iran that included 19 MBL-producing P. aeruginosa reported that 31.5% of their isolates carried the bla VIM gene and 10.5% carried bla IMP , which was higher than that reported in this study [22]. In contrast to our study, a study from Egypt reported that none of their P. aeruginosa was positive for the bla VIM gene [20]. In the present study, 9.4% of our isolates were positive for the bla NDM-1 gene, which is lower than that reported from India (27%) [31].…”
Section: Discussioncontrasting
confidence: 99%
“…A wide range of resistant mechanisms make P. aeruginosa swiftly change to the selective environmental pressure and makes it resistant to several classes of antibiotics. In this study, 77.5% of the isolates were found to be resistant to imipenem, which corroborates to that reported from Egypt (78.3%) [20] and China (73.3%) [21]. Compared to other studies from the Asia-Pacific region including Iran (25.2%) [22], China (17.1%, 43.3%) [23,24], Japan (28.5%) [25] and Taiwan (16%) [26], this study reported a much higher resistance toward imipenem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…El-Bialy et al reported similar results concerning the effectiveness of amikacin and imipenem [25]. These results disagreed with Abaza et al who reported higher resistance to imipenem (78.3%) [37]. Improper use of antibiotics explains the high resistance found among isolates.…”
Section: Discussionmentioning
confidence: 91%
“…This can be interpreted in terms of anaerobic growth of the bacteria obtaining energy from oxidation of sugars thus rendering dif iculty of eradication [21]. Amany et al 2017 [26], found that acquired infection rate in ICU was higher than other hospital wards. The ubiquitous nature, including the ability to survive in a moist environment and resistance to many antibiotics, makes P. aeruginosa a common pathogen in the ICUs of hospitals.…”
Section: Discussionmentioning
confidence: 99%